Le Fort III in Syndromic Craniosynostosis: Cost Comparison of Distraction Osteogenesis Versus Single-Stage Internal Fixation Techniques. Issue 2 (May 2019) - Mosa, Adam J.; Zellner, Elizabeth; Ho, Emily S.; Fisher, Mark D.; Phillips, John H.; Forrest, Christopher R.
Purpose: In syndromic craniosynostosis, the Le Fort III osteotomy is used to correct dental/skeletal imbalance, improve exorbitism, and increase the airway. The purpose of this study is to perform a cost comparison between the standard technique of single-stage rigid internal fixation and distraction osteogenesis (DO) in the Le Fort III osteotomy in this patient population. Method: Hospital cost accounting databases were queried for patients undergoing single-stage advancement (SS) or DO from 2007 to 2016. Nominal cost data were adjusted using the Bank of Canada Consumer Price Index. Reported costs represented the full length of stay for all utilization per patient. Demographic information and cost data for single-stage osteotomy and DO were compared. Results: Total costs for single-stage (n = 8) were higher than distraction (n = 6; mean $CAD57 825 vs $38 268, P < .05). Intensive care unit (ICU) costs for single-stage were significantly higher than distraction (mean, $17 746 vs $5585, P < .005). Distraction cases had higher operating room (OR) costs than single stage, but the difference was not significant (mean, $12 540 vs $9696). Length of stay was significantly longer for SS patients (mean, 11 days vs 7 days, P < .05). Conclusions: This single-institution retrospective cost analysis indicates standard SS rigid internal fixation Le Fort III is more costly than DO. Despite higher OR costs, prolonged ICU and hospital stay was the primary reason behind this difference. This information may be of benefit when advocating for new technology perceived as high cost.